Reflection and Evaluation of Distance Education in School - Chahin-Dörflinger, Fatima (International Dialogues on Education Journal, 2020)
When schools in Germany were closed in Spring 2020 due to the COVID-19 pandemic, distance teaching and learning was implemented. Teachers and schools strived to recreate learning programs and education in a new and unknown way. To learn about ways that distance learning can work well for students and schools, several teachers and principals started to evaluate their distance teaching and learning with scientific support of the evaluation service center of the Institute of Educational Analysis (IBBW). The findings of this action research led to a model of orientation for reflection and development of digital distance teaching and learning in schools.